The environmental degradation of adhesive joint / Muhazli Muhammad and Rosli Yusof - Muhammad, Muhazli; Yusof, Rosli (Faculty of Mechanical Engineering, 1999)
Adhesive joints are expected to retain a significant proportion of their load bearing capacity for the entire duration of the service life of the bonded structure. However, service conditions can often involve exposure to combinations of static or fatigue load and hostile environment (marine, hot/wet, weathering or chemical). It is therefore essential that the end user and the adhesive manufacture possess the necessary tools for selecting and characterising an adhesive system, to ensure reliability bond performance under hostile operating condition. Optimising joint performance requires an understanding on the failure mechanisms involved in environment degradation, and validated test methods and design methodologies suitable for predicting material degradation and life expectancy. The general consensus is that wider used of adhesive technology has been impeded by a lack of reliable test methods, accelerated ageing procedures, quantitative data and predictive analysis for determining durability of structural adhesive joints to hostile environments.